Sustainability and Determinants of Entrepreneurship Propensity Among Young Graduates in Nigeria - Caleb M. Adelowo; Alfred Henrico (SAGE Open)
Creating and Sustaining entrepreneurship inclination among young and educated people are important pillars for building strong and prosperous economy. Studies have shown consistent improvement in entrepreneurship interest and practices among Nigerian undergraduates since the introduction of entrepreneurship education in 2006. However, it remains unclear whether they are able to sustain the interest after graduation and more importantly whether entrepreneurial interest is actually translated to self-employment. This study examines entrepreneurial inclination and practice among fresh graduates using a large-scale cross-sectional data collected through a self-reported validated structured questionnaire. The results showed higher entrepreneurial intention among the graduates than in previous datasets. Further analysis revealed that parent’s business experience, apprenticeship, having a business plan, and entrepreneurship education are positive significant factors influencing entrepreneurship activities among the graduates. Expectedly, age of the graduates is also found to be negatively significant to their entrepreneurial inclination, while gender and marital status are not significant. The study concludes with appropriate managerial and policy implications and suggests measures to sustain and strengthen entrepreneurship ecosystems in the country.